Turning conflicts into cooperation? The role of adaptive learning and deliberation in managing natural resources conflicts in Nepal. (22nd July 2019) - Ojha, Hemant R.; Bhusal, Prabin; Paudel, Naya S.; Thompson, Paul M.; Sultana, Parvin
ABSTRACT: Conflicts over natural resources are likely to escalate under changing socio-economic contexts and climate change. This paper tests the effectiveness of what we term Adaptive Learning and Deliberation (ALD) in understanding and addressing conflicts over the local management of forests and water, drawing on experimental work in Nepal. Based on a three-year action research project, the paper offers policy and practical insights on how complex and protracted conflicts can be addressed through the researcher-facilitated enquiry and deliberative processes that form the core of the ALD approach. The conflicts included in the study are a result of diverse environmental, political and economic factors. We analyze experimental practices in two sites, where our research team facilitated the ALD process, gathering evidence in relation to conflicting institutional issues, all of which was then fed into researcher-mediated and evidence-informed deliberations on conflict management. The analysis shows that the ALD process was helpful in rearranging local institutions to accommodate the interests of the conflicting groups and, to some extent, to challenge some of the underlying exclusionary provisions of forest and water institutions in Nepalese society. We also identify three key limitations of this approach – transaction costs, the need for strong research and facilitative capacity within the research team, and researchers' engagement with the conflicting stakeholders. Key policy insights Natural resource-based conflicts are intensifying in Nepal in recent years, due to heavy reliance of people on these resources for livelihoods, poor governance, and protection-oriented policies. Improved ways to facilitate cooperation among conflicting stakeholders are needed, as standard methods have often failed to address socio-environmental drivers of conflicts. The ALD approach can potentially help mitigate conflict and foster cooperation in natural resource management.